2017
DOI: 10.1002/jbmr.3364
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Deficiency–Mediated M2 Macrophage Osteoclastogenesis Contributes to M1/M2 Ratio Alteration in Ovariectomized Osteoporotic Mice

Abstract: In this study, for the first time we discovered that the M1/M2 macrophage phenotype ratio is increased in bone marrow of ovariectomized (OVX) osteoporotic C57BL/6 mice. Considering estrogen is the main variable, we assumed that estrogen participated in this alteration. To determine whether and how estrogen contributes to the change of the M1/M2 ratio, we first isolated bone marrow macrophages (BMMs) from mice femur and stimulated the cells with lipopolysaccharide (LPS)/interferon γ (IFN-γ) for M1 polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 50 publications
3
80
0
Order By: Relevance
“…We assume that the immunomodulatory and anti-inflammatory activities of physalin D were likely to be realized by its regulation of macrophage polarization toward the M2 phenotype shift. One of our recent studies interestingly showed that M1/M2 ratio alteration also contribute to the pathogenesis of estrogen-deficiency-induced osteoporosis which further reinforced the idea that M1/M2 polarization is a target of great potential in treating related chronic diseases (Dou et al, 2018).…”
mentioning
confidence: 61%
“…We assume that the immunomodulatory and anti-inflammatory activities of physalin D were likely to be realized by its regulation of macrophage polarization toward the M2 phenotype shift. One of our recent studies interestingly showed that M1/M2 ratio alteration also contribute to the pathogenesis of estrogen-deficiency-induced osteoporosis which further reinforced the idea that M1/M2 polarization is a target of great potential in treating related chronic diseases (Dou et al, 2018).…”
mentioning
confidence: 61%
“…Studies showed that M1 macrophages could down‐regulate osteoclastogenesis (47), and conversely, osteoclast‐related fusion protein may decrease M1 macrophage polarization (48). Moreover, estrogen‐deficient M2 macrophages could lead to the increased osteoclast differentiation (49). These studies exposed the potential role of M1 macrophages in inhibiting osteoclast function.…”
Section: Discussionmentioning
confidence: 99%
“…The polarisation of pro-inflammatory macrophages M1 to anti-inflammatory macrophages M2 is indicative of endochondral ossification in the long bone fracture model (Cordova et al, 2017;Loi et al, 2016;Schlundt et al, 2018). In OVX mice, M1 polarisation is enhanced while M2 polarisation is impaired, leading to increased M1/M2 ratio in the bone marrow (Dou et al, 2018). The present study results revealed that the vibration treatment brought the number of M2 macrophages to normal levels, as shown by similar CD206 level to SHAM, and induced higher CD206 expression as compared to OVX rats (Fig.…”
Section: Discussionmentioning
confidence: 99%